The Effect of Customer Loyality and Satisfaction's Factors in Visiting Mall XYZ - Farony, Rivan; Suef, Mokh.; Ratnasari, Vita (IPTEK Journal of Proceedings Series, 2020)
Mall Success can be seen with a large number of mall visitors and visitors coming. In this case, one of the malls in the Tidar area of Surabaya is more important than most of the malls in general in the city of Surabaya. At the XYZ mall area, visitors are seen lonely from day to day, this is a big question mark whether visitors are satisfied to receive a compilation of visiting the mall. For this reason, the satisfaction of visitors and customers in the mall is an important factor in determining the buying and selling activities in the mall. The research offered suggests about customer satisfaction and customer loyalty proposed by, hedonic value, Relaxation Value, socialization value, Utilitarian Value. This can affect the purchasing power of consumers to buy at the mall. Satisfaction can provide a supported spending will, thus providing a significant turnover of money. By creating a sense of satisfaction can generate customer loyalty in the mall. This research was conducted by distributing questionnaires to visitors or customers who have come to the XYZ mall. The method used in this research is Structural Equation Modeling. by Processing data using Smart PLS software because the research model is complex. The findings in this study are the outcome variable, Hedonic Value, Relaxation Value, and Socialization Value regarding customer satisfaction and customer loyalty, while the Utilitarian Value only has a significant effect on customer satisfaction. The results of this study are expected to make the mall management considerations to develop the right strategy in increasing the number of visitors and customers to come to the mall.